UMA INTRODUÇÃO DE TÓPICOS DE FÍSICA MODERNA NO ENSINO MÉDIO - Sonza, Aline Picoli (2007)
This work presents a communication of the experience about the development and applications of some topics of Modern Physics in the Secondary School. This study was done from different aspects with the aim to analyze how the Modern Physics is treated in the Secondary School, what the didactic books present about this subject, a development of didactic lessons and their application in the classroom. In a first time, it was done an investigation among the teachers of the Secondary School of the Santa Maria RS about some questions in the education/learning of Modern Physics. From these answers, it was done a carefully analysis of the didactic books more used in the Schools. Following, was developed a didactic group of lessons with introductory topics of Modern Physics based on the didactic books, digital educational information s and scientific newspapers. These lessons present a simple language and questions related with the quotidian of the students, instigating the scientific investigation. Finally, these lessons are applied in a previous selected group of students of the second year of the Secondary School on the Escola Estadual Cilon Rosa from Santa Maria RS. The lessons are presented in four (04) classes, where the teacher used, additionally of the explanation classes, virtual activities, newspapers and discussions about the theme. This work shows a high interest of the Secondary School teachers about Modern Physics, as the high determination of the students on the developed activities.